Analysis of the accumulation, depuration and methylation of mercury in pacific oysters (Crassostrea gigas) and clams (Meretrix meretrix) using the two‐compartment kinetic model. (15th February 2021) - Liu, Tianhong; Su, Han; Wang, Ying; Li, Xiao; Sun, Yuanqin; Li, Hongyan
Abstract: In this study, the accumulation, depuration and methylation of mercury in Crassostrea gigas and Meretrix meretrix were analysed and evaluated using the two‐compartment kinetic model through exposure in mercury chloride (HgCl2 ) solution and depuration procedure in seawater. The results showed that the accumulation and depuration of mercury in organisms were related to the dissolved inorganic Hg(II) content with accumulation delay. It was suggested that the two organisms formed methylmercury (MeHg) when exposed to Hg(II) that is not only formed by anaerobic bacteria in marine sediments. The peak value of MeHg appeared in the depuration phase. The accumulation of C. gigas was stronger than that of M. meretrix, with a peak value of 37.86 ± 3.29 μg/g and 14.48 ± 0.29 μg/L respectively. Crassostrea gigas also had a stronger methylate ability. According to the reference dose for MeHg determined by the United States Environment Protection Agency along with model calculations, when the concentration of Hg in the water reaches 0.2 μg/L, the cultured M. meretrix would be safe for consumption, while cultured C. gigas should be depurated before marketing due to the higher content of MeHg (0.50 mg/kg). Therefore, the two‐compartment kinetic model could be used to monitor the Hg and MeHg content of bivalves when the concentration of Hg in seawater is known.